LEGENDA TANJUNG MENANGIS: RESEPSI MASYARAKAT, NILAI PRAGMATIS, DAN RELEVANSINYA DENGAN PENGEMBANGAN BAHAN AJAR SASTRA - Ahmad Sirajudin (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2014)
One of the oral folklores in the form of story which have developed in the community of Samawa ethnic group is the legend of Tanjung Menangis [the Crying Peninsula]. As a folklore, the legend is thought as containing and expressing pragmatic values. The current study aimed at describing: 1) pragmatic values contained in the legend of Tanjung Menangis; 2) reception of Samawa ethnic community towards the values contained in the legend of Tanjung Menangis; 3) relevance of the pragmatic values in the legend of Tanjung Menangis to the content of literature learning at Senior High School. The study was an ethnographic study which was descriptive in nature. The data were collected by using interview, observation, and documents study, and analyzed descriptive-qualitatively through such steps as data transciption, data identification, data reduction, data interpretation, and conclusion drawing. The data analysis and discussion resulted in three points of conclusion, i.e.: (1) the legend of Tanjung Menangis contains pragmatic values: faith, moral and ethics, social and culture, goodness, smartness and logic; (2) Samawa ethnic community has varied opinions towards the existence of the legend of Tanjung Menangis and pragmatic values contained in the legend; (3) the pragmatic values contained in the legend of Tanjung Menangis has relevance to the content of literature learning at Senior High School, especially old prose literature.Key words: legend, community reception, pragmatic value, literature learning materials